Evaluation of Physico-Mechanical-Combustion Characteristics of Fuel Briquettes made from blends of Areca Nut Husk, Simarouba Seed Shell and Black Liquor - Santhosh Ujjinappa; Lingadhalli Krishnamurthy Sreepathi (International Journal of Renewable Energy Development, 2018)
In order to utilize the agro residues and non-edible oil seed shells for the energy purpose, Areca Nut Husk (ANH) and Simarouba Seed Shell (SSS) are considered as raw materials and pulp production industry byproduct Black liquor (BL) as a binder for the production of fuel briquettes. The cylindrical briquettes were produced in four different blending proportions at 3 different pressures between 60 MPa to 80 MPa and various briquette properties were evaluated. The mathematical regression equations between the independent variables (blending proportion and compacting pressure) and briquette properties were developed. The R2 values for the regression equation between independent variables and (Briquette properties) compressed density, relaxed density, relaxation ratio, shattering index and compressive strength were 0.945, 0.743, 0.646, 0.862 and 0.839 respectively. The results confirmed that briquette produced with a blending proportion of ANH:SSS:BL=60:40:00 at 80 MPa have better properties. Thus, combustion characteristics such as proximate analysis, ultimate analysis, calorific value were estimated for a briquette produced with a blending proportion of ANH:SSS:BL=60:40:00 at 80 MPa; and compared with Barley and Sawdust charcoal briquettes. The overall results conclude that better quality briquettes can be produced from the blends of ANH and SSS and can be used for several heating applications.Article History: Received Dec 15th 2017; Received in revised form May 16th 2018; Accepted June 3rd 2018; Available onlineHow to Cite This Article: Ujjinappa, S. and Sreepathi, L.K. (2018) Evaluation of Physico-Mechanical-Combustion Characteristics of Fuel Briquettes Made From Blends of Areca Nut Husk, Simarouba Seed Shell and Black Liquor. Int. Journal of Renewable Energy Development, 7(2), 131-137.https://doi.org/10.14710/ijred.7.2.131-137